SINGLE INSTILLATION OF MITOMYCIN C REDUCES 1ST YEAR RECURRENCE FOLLOWING TRANSURETHRAL RESECTION OF NON-MUSCLE INVASIVE BLADDER CANCER - Ather, M. Hammad; Aziz, S; Sulaiman, M N (Journal of Ayub Medical College Abbottabad, 2007)
Objective: To study the impact of single instillation of 40 mg Mitomycin C (MMC-40) within first hour of transurethral resection (TUR), on first year recurrence of non-muscle invasive bladder cancer. Methods: In this study of two groups of patients with similar demographics and tumour profile were compared to assess first year tumour recurrence pattern. Group A received MMC-40 within 30 minutes of TUR. Group B patients only had TUR of bladder tumour. Patients' charts were reviewed for demographic profile, preoperative diagnosis and imaging used, cytological work up, tumour profile both during cystoscopy and imaging used, patients records were also reviewed for all subsequent check cystoscopies for recurrence. Any adjuvant treatments like intravesical chemo/immunotherapy etc. were also noted. The results were analysed using a commercially available statistical package, SPSS„¢. The level of significance was ï‚£0.05. Results: There were 29 and 46 patients in group A and B respectively. The demographic profile in terms of age, gender distribution, tumour characteristics (size, site, multiplicity) and pathological evaluation including, tumour grade and presence of carcinoma in situ were similar (p<0.4 and p<0.5) respectively. The first year recurrence rate in group A was 15% whereas it was 37.4% in group B (p<0.04). Conclusions: The first year recurrence rate is significantly decreased if MMC-40 is instilled following TUR. MMC-40 is safe and cost effective. Most low grade, low volume tumours would not require any further treatment if MMC-40 is given immediately following TUR. Key words: non-muscle invasive bladder cancer, single instillation of chemotherapeutic agent, recurrence